Kajian Literatur: Model Flipped Classroom dalam Pembelajaran IPAS di Sekolah Dasar - Relandia, Monix Karina; Muharram, Muhammad Rijal Wahid; Putri, Agnestasia Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to examine the application of the flipped classroom model in learning Natural and Social Sciences (IPAS) at the elementary school level. IPAS learning is expected to not only focus on delivering material, but also be able to foster activeness, curiosity, and optimal student involvement. The flipped classroom model is an innovative alternative that can reverse conventional learning patterns, by presenting learning materials first through digital media to be studied independently at home, then using face-to-face time in class for discussion, questions and answers, and collaborative problem solving. This study uses a qualitative approach with data collection techniques in the form of observation and literature study of five scientific articles published in 2020–2025. The results of the study show that the flipped classroom model has great potential in improving cognitive learning outcomes, conceptual understanding, and active involvement of students in IPAS learning in elementary schools.